Program Pelatihan Sumber Daya Manusia di Desa Wisata Angsana, Desa Setu, Kabupaten Bogor - Matthew Tristan Afrianto; Livia Christy Harsana; Justin, Lionel; Lukas Gavrila Jefferson; Setiawan, Budi (Yayasan Literasi Sains Indonesia, 2024)
Angsana Tourism Village is one of the many tourist villages in Setu Village, Jasinga District, Bogor Regency. With the existence of this tourist village, it is a dream to provide opportunities and possibilities for the surrounding community to utilize the potential and resources contained in this tourist village to support the sustainability and growth of tourism in the Angsana tourist village. The community service method used is a participatory qualitative method, with data collection techniques of observation, surveys and training. The development plan for this tourism country is Human Resources training. In this training, it can provide new knowledge for the people of Angsana Village. The training was carried out to equip the residents of Angsana Village regarding homestay standardization starting from the introduction of making beds, steps in making beds, and simulating making beds and so on with table set up and bathroom cleaning training. From a student's perspective, this training allows them to remember the lessons taught and apply the knowledge gained in the Angsana village community.